Dynamic real-time in vivo confocal laser endomicroscopy of the fallopian tube during laparoscopy in the prevention of ovarian cancer. (September 2017) - Chene, Gautier; Chauvy, Lauriane; Buenerd, Annie; Moret, Stéphanie; Nadaud, Béatrice; Chabert, Philippe; Lamblin, Gery
Abstract: Objectives: Recently it has been postulated that most ovarian cancers have a tubal origin. The identification of preinvasive tubal lesions would be of great interest in the early diagnosis of ovarian cancer. Optical biopsy has been developed and validated in the detection of precancerous lesions (such as Barrett's oesophagus). The first objective of this study was to assess the feasibility of optical biopsy in the study of fallopian tubes during laparoscopy. The second objective was to describe the images in benign premalignant and malignant tubes with a histopathological and immunohistochemical (p53 and Ki67 expressions) correlation. Study design: In this prospective study, 40 patients undergoing laparoscopic salpingectomy for benign conditions (benign hysterectomy), prophylactic conditions (BRCA mutation) or in case of pelvic cancers were included after obtaining informed and signed consent prior to surgery. The optical biopsy was performed on the fimbria of each tube in and ex vivo . A correlation was made with the histopathological and immunohistochemical analysis. Results: The feasibility of optical biopsy was always confirmed during laparoscopy. The optical biopsy iconography revealed different images in benign tubal epithelium (well-defined black and grey structure), in adenomatoid tumour (tortuous architectural organization), in STIC precancerous lesion (enlarged, irregular and pleomorphic cells, dilated and distorted vessels) and in tubal metastasis of high grade serous ovarian cancer (dark neoplastic cells irregular in size and shape) Conclusions: Optical biopsy may be the first emerging mini-invasive technology that could detect tubal lesions and may be considered as a promising tool in the early detection of ovarian cancer.